Flame-retardant mechanism of zinc borate and magnesium hydroxide in aluminum hypophosphite–based combination for TPE-S composites. (May 2019) - Cheng, Xi; Wu, Jianming; Yao, Chenguang; Yang, Guisheng
Aluminum hypophosphite combined with melamine cyanurate and poly(phenylene oxide) was applied to flame retard TPE-S system (blends of SEBS and polyolefin). TPE-S containing 16 wt% aluminum hypophosphite, 20 wt% melamine cyanurate, and 10 wt% poly(phenylene oxide) pass a V-0 rating in the UL-94 test and its limiting oxygen index value is 28.2%. Zinc borate and magnesium hydroxide were added to modify the AHP/MCA/PPO formulation. Thermogravimetric–Fourier transform infrared analysis tests showed that aluminum hypophosphite and melaminecyanurate acted in gaseous phase while aluminum hypophosphite and poly(phenylene oxide) helped to form char residue. TPE-S/AHP/MCA/PPO significantly decreased the heat release rate (reduction in peak heat release rate from 2001 to 494 kW m −2 ). Scanning electron microscopy/energy dispersive spectrometry results demonstrated that zinc borate and magnesium hydroxide promoted to retain more P and O elements in residue. Zinc borate and magnesium hydroxide in AHP/MCA/PPO formulation enhanced the char formation and reduced gas evolution of TPE-S, thus deteriorating the combination between gaseous phase and condensed phase.